Representation of Political System in Song Lyrics of “Only The Young”: A John Fiske Semiotic Analysis - Bully, Nurlina Ahmad; Suherman, Ansar; Maulana, Harry Fajar (Jogjakarta Communication Conference (JCC), 2025)
This study shows the meaning of the political system in the lyrics of the song